ON q-DEFORMATED HORMANDER MULTIPLIER THEOREM (Journal of Mathematics Mechanics and Computer Science, 2025)
The main purposes of this work, we introduce the q-deformed Fourier multiplier Ag defined on the space L2q(Rq) through the framework of the q2-Fourier transform, while also extending the functional setting of Lpq(Rq) with 1 ≤ p < ∞. Our approach provides a natural extension of classical Fourier multiplier theory into the q-deformed setting, which is relevant in the context of quantum groups and noncommutative analysis. Furthermore, we establish several key q-analogues of classical harmonic analysis inequalities for the q2-Fourier transform, including the Paley inequality, Hausdorff-Young inequality, Hausdorff-Young-Paley inequality, and Hardy-Littlewood inequality. These results not only generalize their classical counterparts but also open new avenues for analysis on q-deformed spaces. As a significant application, we prove a q-deformed version of the Ho¨rmander multiplier theorem, which provides sufficient conditions for the boundedness of multipliers in the q-deformed setting. This work sets the stage for further developments in the field of q-deformed harmonic analysis.
Keywords: q-Jackson integral; q-caclulus; Fourier multiplier; inequality; multiplier; Hausdorff-Young inequality